COORDINATION CHEMISTRY OF Ni(II), Cu(II) AND Zn(II) IONS WITH N202 AND N403 DONOR LIGANDS - Liew Yew, Zion (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Three ligands have been formed by the 1: 2 molar condensation reactions of salicyaldehyde with hydrazine, o-phenylenediamine or carbohydrazide. The polydentate ligands are N, N'-bis (salicyaldehyde)-hydrazine (1), N, N'-bis (salicyaldehyde)-ophenylenediamine (2) and N, N'-bis (salicyaldehyde)-carbohydrazide (3). These ligands form complexes in the 1: 1 molar ratio with nickel, copper and zinc ions. The complexes have been characterized by IR, 1H NMR, UV-Visible spectral data, molar conductivity and elemental analysis. The spectroscopic study of the ligands and their transition metal complexes with nickel, copper and zinc are discussed in connection with the structural changes which occur due to complexation.